#TITLE_ALTERNATIVE# - LEONORA (NIM : 15308059), ELISABETH
Leachate has a very high organic content, so leachate treatment before being released into the environment is very essential. Existing condition for leachate treatment is usually done only by using stabilization ponds with relatively long retention time. Coagulation-flocculation can be an alternative for leachate’s pre-treatment process, reducing leachate’s organic loading for the next treatment units. The aim of this study is to investigate the effectiveness of coagulation–flocculation process as leachate’s pre–treatment process with aluminium sulfate, PAC, and FeCl3 as coagulants. The study was conducted by using a laboratory scale jar-test method. As the results of the study, the highest removal efficiency for total COD was occured on 4500 mg/L on addition of alum and FeCl3, also on 3500 mg/L on addition of PAC. However, these dose are inefficient because the numbers are very high and the volume of sludge generated is also very high. Therefore, this research picked an efficient dose for each coagulant. Efficient dose of alum is 500 mg/L with a total COD removal efficiency of 36.14%. Efficient dose of PAC is 300 mg/L with a total COD removal efficiency of 29.79%. By trial using the variations of pH, it is known that the optimum pH for alum is 8. On this pH, by using the efficient dose of alum which is 500 mg/L, the removal efficiency of total COD was increased up to 43,41%. Meanwhile, the optimum pH for PAC was also 8. On this pH, by using the efficient dose of PAC which is 300 mg/L, the removal efficiency of total COD was increased up to 40,18%.